2008
DOI: 10.1007/s12011-008-8251-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Blood Status and Milk, Urine, and Fecal Excretion in Pregnant and Lactating Camel

Abstract: Ten pregnant female camels divided into two groups received, after a 2-week adaptation period, an oral selenium (Se) supplementation (0 and 2 mg, respectively) under sodium selenite form for 6 months from the three last months of gestation up to the three first months of lactation. Feed intake was assessed daily. Blood samples and body weight were taken on a biweekly basis, both in dams and their camel calves after parturition. Feces and urine samples were collected monthly and milk on a biweekly basis. The Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
4
33
3
Order By: Relevance
“…In the same area than our study, Athamma et al (2012) found 37.2 and 46.1 ng/mL in dam and new-born respectively. In Emirates, with camel receiving 2mg/day oral Se supplementation, the Se serum concentrations in camel calf at parturition were 273.2 ± 48.0 and 106.3 ± 26.5 ng/mL in the treated and control groups respectively (Seboussi et al, 2009a) i.e. a similar proportion than in dams.…”
Section: Results and Discussion Selenium In Bloodmentioning
confidence: 88%
See 4 more Smart Citations
“…In the same area than our study, Athamma et al (2012) found 37.2 and 46.1 ng/mL in dam and new-born respectively. In Emirates, with camel receiving 2mg/day oral Se supplementation, the Se serum concentrations in camel calf at parturition were 273.2 ± 48.0 and 106.3 ± 26.5 ng/mL in the treated and control groups respectively (Seboussi et al, 2009a) i.e. a similar proportion than in dams.…”
Section: Results and Discussion Selenium In Bloodmentioning
confidence: 88%
“…They stated also on the specific Se metabolism in camel regarding the toxicity threshold (Seboussi et al, 2009b) and the supplementation which cannot be applied directly from cattle requirements. Moreover, those former results obtained in Emirates (Seboussi et al, 2009a) were reported in a context of Se deficiency widely observed in the field with numerous cases of white muscle disease or heart failure due to lack of Se in the mother's diet, and furthermore partly with dams receiving before calving an oral Se supplementation under selenite form. In Saudi Arabia, where selenium status in human population was regarded as low (Al-Saleh, 2000), selenium deficiency was regularly incriminated also in grazing livestock.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations